Structural Properties of Cruciferin and Napin of Brassica napus (Canola) Show Distinct Responses to Changes in pH and Temperature - Perera, Suneru P. (Plants (Basel), 2016)
The two major storage proteins identified in Brassica napus (canola) were isolated and studied for their molecular composition, structural characteristics and the responses of structural features to the changes in pH and temperature. Cruciferin, a complex of six monomers, has a predominantly β-sheet-containing secondary structure. This protein showed low pH unstable tertiary structure, and distinctly different solubility behaviour with pH when intact in the seed cellular matrix. Cruciferin structure unfolds at pH 3 even at ambient temperature. Temperature-induced structure unfolding was observed above the maximum denaturation temperature of cruciferin. Napin was soluble in a wider pH range than cruciferin and has α-helices dominating secondary structure. Structural features of napin showed less sensitivity to the changes in medium pH and temperature. The surface hydrophobicity (S(0)) and intrinsic fluorescence of tryptophan residue appear to be good indicators of cruciferin unfolding, however they were not the best to demonstrate structural changes of napin. These two storage proteins of B. napus have distinct molecular characteristics, therefore properties and functionalities they provide are contrasting rather than complementary.